Measurement of Auroral Electric Fields with an Antarctic Sounding Rocket S-310JA-7. 1.DC Electric Field - Ogawa, Toshio; Makino, Masahiko; Hayashida, Sachiko; Yamagishi, Hisao; Fujii, Ryoichi; Fukunishi, Hiroshi; Hirasawa, Takeo; Nishino, Masanori (1981)
P(論文) The results are given on the DC electric field in an active auroral arc and outside the equatorside of it observed with two pairs of orthogonal double probes launched by an Antarctic sounding rocket S-310JA-7 at 191550 UT on March 27,1978 at Syowa Station. The north-south component of the observed electric field was northward (equatorward) in the arc, and southward (poleward) outside the equatorside of the arc with a magnitude of about 20mV/m. The east-west component was mostly westward throughout the rocket flight and smaller (about 5mV/m) in the arc and larger (about 50mV/m) outside the arc. Anticorrelation of the electric field and precipitating particles is evident. An examination of the oppositely inward directed electric fields in the meridional cross section suggests an electrostatic potential configuration responsible for the acceleration of precipitating particles. The observed westward component would have been originated in the large scale earthward plasma convection in the magnetosphere. departmental bulletin paper